Inside man [videorecording (Blu-Ray)] - Grazer, Brian, 1953-; Gewirtz, Russell; Lee, Spike; Washington, Denzel, 1954-; Owen, Clive; Foster, Jodie; Plummer, Christopher; Dafoe, Willem; Ejiofor, Chiwetel; Blanchard, Terence (Universal Studios Home Entertainment, 2009)
The perfect bank robbery quickly spirals into an unstable and deadly game of cat-and-mouse between a criminal mastermind, the hostages, a determined detective, and a power broker with a hidden agenda. As the minutes tick by and the situation becomes increasingly tense, one wrong move could mean disaster for any one of them.